2022
DOI: 10.3390/stresses2010009
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses to Drought, Salinity, and Heat Stress in Plants: A Review

Abstract: On the world stage, the increase in temperatures due to global warming is already a reality that has become one of the main challenges faced by the scientific community. Since agriculture is highly dependent on climatic conditions, it may suffer a great impact in the short term if no measures are taken to adapt and mitigate the agricultural system. Plant responses to abiotic stresses have been the subject of research by numerous groups worldwide. Initially, these studies were concentrated on model plants, and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
137
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(142 citation statements)
references
References 189 publications
5
137
0
Order By: Relevance
“…S6a ). It has previously been described that heat stress and salt stress trigger the activation of common genes related with osmotic stress, oxidative stress and leaf physiology, and particularly, photosynthetic activity in plants such as olive, rice, and coffee [ 71 , 72 ]. In this study we found that DMRs were enriched in genes related to transcription factor regulation and activity as well as generators of metabolites and energy for heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…S6a ). It has previously been described that heat stress and salt stress trigger the activation of common genes related with osmotic stress, oxidative stress and leaf physiology, and particularly, photosynthetic activity in plants such as olive, rice, and coffee [ 71 , 72 ]. In this study we found that DMRs were enriched in genes related to transcription factor regulation and activity as well as generators of metabolites and energy for heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Above the normal temperature range, plants restrict growth, development, and physiological cellular metabolism. Heat stress raises the morbidity and mortality of plants and deteriorate their quality [ 6 , 7 , 8 ]. If the duration of heat stress increases, it may cause irreversible changes, such as cellular destruction, in plant cells.…”
Section: Introductionmentioning
confidence: 99%
“…Drought stress is a frequent abiotic stress that restricts crop growth and yield around the globe ( Yao and Wu, 2016 ). In plants, drought triggers a complex set of molecular responses that starts with stress detection, progresses through a signal transduction cascade, and ends with physio-morphological changes at the cellular level, such as stomatal closure, cellular respiration activation, and inhibition of cell growth and photosynthesis ( Lamaoui et al, 2018 ; dos Santos et al, 2022 ). Plants can also generate and accumulate certain metabolites that are specifically engaged in stress tolerance when they are subjected to drought ( da Silva et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%